Thermal diffusivity measurement of BSCCO superconductor (85 to 300 K) using PVDF transducer - Haydari, Mehdi; Abd. Moksin, Mohd Maarof; Mat Yunus, Wan Mahmood; Grozescu, Ionel Valeriu; Hamadneh, Imad; Shaari, Abdul Halim (Universiti Putra Malaysia Press, 2004)
Thermal diffusivity measurement of the Bi-Pb-Sr-Ca-CII-O superconducting ceramic sample is reported. In this work camera flash and polyvinylidene difluoride (PVDF) film were respectively used as heating source and pyroelectric detector. The theoretical signal calculation based on Dirac- function approximation for camera flash temporal profile was used to deduce the thermal diffusivity. The measurement was done from 85 K to room temperature. The thermal diffusivity curve shows a dip at the resistive transition onset temperature and a cusp at the zero-resistance temperature. Thus, we found that the PVDF transducer is very effective in determining the normal-to-superconductor transition phenomena and also for the measurement of the thermal diffusivity of the superconducting samples at low temperatures.